Approach to Child with Constipation and Management Update (Bangladesh Journal of Child Health, 2018)
Constipation is a common problem in childhood that need frequent visit to pediatrician. The objective of this review is to provide the general pediatrician an overview of constipation in children discussing the etiology, patient evaluation and management. This review provides an approach to a child with constipation based on the best available evidence from electronic literature searches. Most common etiology of childhood constipation is functional and it needs no laboratory tests. Laboratory investigations are to be done if there are any alarming signs. Management is to do disimpaction if fecal impaction present, then long term maintenance therapy along with behavioral therapy ensure full recovery.Bangladesh J Child Health 2017; VOL 41 (3) :170-180